Professional Development Programmes: Practices and Impacts - Yadav, Binod Kumar (KMC Journal, 2024)
Professional programmes like trainings, workshops, symposiums, conclaves, conferences, and similar development opportunities play a significant role in enhancing faculty professional skills and ultimately nurturing quality ecology within an institution. This study attempted to analyze the practice of such programmes during the last five years at J S Campus Lahan, Siraha, how they have been practically prioritized by the faculty members and this institution, and what impacts are being observed so far. It applied the mixed research design and the sample of study included faculty members, RMC coordinator, and Heads of the institution. The data from them were collected through interview and questionnaire, and also from the RMC/administrative records about the programme practice and the graduate products. The analysis was developed discussing the nature of the programmes, their occurrences, participation of the faculty, and the impacts on the faculty performance and the institution as well. The results showed that such programme practice was good but its products revealed the worst, an action to be considered soon. Finally, some initiatives are recommended for healing such a bizarre research scenario with this leading institution of Madhesh Province.